The Susceptibility Simulation of Ochratoxin A and Aflatoxins Contamination on Fermented and Unfermented Cocoa Beans in High Storage Humidity - Francis M.C. Sigit Setyabudi; H. Adhianata; Sardjono Sardjono; W. Mahakarnchanakul (Indonesian Food and Nutrition Progress, 2017)
Most of Indonesia’s cocoa beans has been produced through fermentation. Various metabolite end products such as alcohol, lactic acid, and acetic acid are produced during cocoa beans fermentation. These metabolites would induce different chemical characteristic of fermented cocoa beans. In this research, parameters evaluated were OTA and AFs contamination to determine the susceptibility of fermented and unfermented cocoa beans on OTA and AFs production during storage simulation. To investigate the susceptibility, this research was conducted on storage simulation condition which was 91% of relative humidity. It is hypothesized that metabolic end-products from the breakdown substrate during fermentation process have an effect on mycotoxin production by fungi.This is the first report of ochratoxin A and aflatoxins contamination susceptibility in fermented and unfermented cocoa beans. Fermented cocoa beans were more susceptible to AFs contamination. The highest AFs contamination was found in fermented inoculated cocoa beans after 10 days storage. Unfermented cocoa beans were more susceptible to OTA production. The highest OTA contamination was found in unfermented inoculated cocoa beans after 15 days storage.The results of the present study indicated a promising different potential between ochratoxin A and aflatoxins production in fermented and unfermented cocoa beans during simulation storage condition, suggesting the existence of limiting factors on the accumulation of ochratoxin A and aflatoxins in the beans by the metabolic-end products produced during fermentation.